Power Series Diff

From Grad Wiki
Revision as of 10:43, 12 May 2015 by Matt Lee (talk | contribs) (Created page with "{| class="mw-collapsible mw-collapsed" style = "text-align:left;" !The pdf |- | <source lang = "latex"> %% LyX 2.1.3 created this file. For more info, see http://www.lyx.org/...")
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search
The pdf

<source lang = "latex"> %% LyX 2.1.3 created this file. For more info, see http://www.lyx.org/. %% Do not edit unless you really know what you are doing. \documentclass[11pt,english]{amsart} \usepackage[T1]{fontenc} \usepackage[latin9]{inputenc} \usepackage[letterpaper]{geometry} \geometry{verbose,tmargin=1in,bmargin=1in,lmargin=1in,rmargin=1in} \setlength{\parskip}{\medskipamount} \setlength{\parindent}{0pt} \usepackage{amsthm}

\makeatletter %%%%%%%%%%%%%%%%%%%%%%%%%%%%%% Textclass specific LaTeX commands. \numberwithin{equation}{section} \numberwithin{figure}{section}

%%%%%%%%%%%%%%%%%%%%%%%%%%%%%% User specified LaTeX commands. %% LyX 1.5.6 created this file. For more info, see http://www.lyx.org/. %% Do not edit unless you really know what you are doing.



\makeatletter %%%%%%%%%%%%%%%%%%%%%%%%%%%%%% Textclass specific LaTeX commands. \numberwithin{equation}{section} %% Comment out for sequentially-numbered \numberwithin{figure}{section} %% Comment out for sequentially-numbered

%%%%%%%%%%%%%%%%%%%%%%%%%%%%%% User specified LaTeX commands. %TeX command: LaTeX %The first set of commands determines the overall look of your document.

\setlength{\textwidth}{6.1in} \setlength{\oddsidemargin}{0pt} \setlength{\evensidemargin}{0pt} \setlength{\hoffset}{4pt}


\usepackage{amsthm}


%The next two lines make it easy for me to put comments into your drafts. \@ifundefined{definecolor}

{\@ifundefined{definecolor}
{\usepackage{color}}{}

}{}

\def\comment#1{{\color{red}{#1}}}

%The following command makes your document double spaced. \renewcommand{\baselinestretch}{1.3}

%The next two groups define "environments" useful for mathematics. \theoremstyle{plain} \newtheorem*{theorem}{Theorem} \newtheorem*{corollary}{Corollary} \newtheorem*{proposition}{Proposition} \newtheorem*{lemma}{Lemma}


\theoremstyle{definition} \newtheorem*{definition}{Definition} \newtheorem*{construction}{Construction} \newtheorem*{notation}{Notation}

%These are a couple of useful definitions. \long\def\ignore#1endignore{} \newcommand{\Z}{{\mathbb{Z}}} \newcommand{\abs}[1]{\left\vert #1\right\vert }

%Now we actually get to stuff that shows up in the document.

\makeatother

\makeatother

\usepackage{babel} \begin{document}

\title{Sums of Power Series Through Differentiation}

\maketitle Okay, we are starting on power series, and there's a few important details about how to find the sum of given power series. Remember, we currently relate almost every power series to the series \[ \frac{1}{1-x}=\sum_{n=0}^{\infty}x^{n}=1+x+x^{2}+\cdots \]


which is convergent for $|x|<1.$

Now, we occasionally get strange forms to evaluate, like:

\textbf{Find the sum of \[ 1.\,\sum_{n=0}^{\infty}nx^{n-1}.\qquad2.\,\sum_{n=0}^{\infty}n(n-1)(n-2)x^{n+2}.\qquad3..\,\sum_{n=0}^{\infty}(n+2)(n+1)x^{n}. \] }

All of these have similar issues.

When we use the power rule for derivatives, we find \begin{eqnarray*} \left[x^{n}\right]' & = & nx^{n-1}\\ \left[x^{n}\right] & = & n(n-1)x^{n-2}\\ \left[x^{n}\right] & = & n(n-1)(n-2)x^{n-3} \end{eqnarray*} and so on. The same holds true when we take the derivative of the infinite sum:

\[ \begin{array}{ccccccl} {\displaystyle \frac{1}{(1-x)^{2}}} & = & {\displaystyle \left[\frac{1}{1-x}\right]'} & = & \left[\sum_{n=0}^{\infty}x^{n}\right]' & = & \sum_{n=0}^{\infty}nx^{n-1},\\ \\ {\displaystyle \frac{2}{(1-x)^{3}}} & = & {\displaystyle \left[\frac{1}{1-x}\right]} & = & \left[\sum_{n=0}^{\infty}x^{n}\right] & = & \sum_{n=0}^{\infty}n(n-1)x^{n-2},\\ \\ {\displaystyle \frac{6}{(1-x)^{4}}} & = & {\displaystyle \left[\frac{1}{1-x}\right]} & = & \left[\sum_{n=0}^{\infty}x^{n}\right] & = & \sum_{n=0}^{\infty}n(n-1)(n-2)x^{n-3}. \end{array} \]


There's a minor detail here. If you plug 0 into $nx^{n-1},$ you just get zero. Similarly, plugging in 0, 1 or 2 into $n(n-1)(n-2)x^{n-3}$ also results in a term of zero. As a result, \[ \sum_{n=0}^{\infty}n(n-1)(n-2)x^{n-3}=\sum_{n=3}^{\infty}n(n-1)(n-2)x^{n-3} \]


since the first three terms are 0. A similar trick works to change the index of the other two.

Now, it's pretty clear the answer to problem 1 is just ${\displaystyle \frac{1}{(1-x)^{2}}.}$ But what about problem 2? This is the key -

\noindent \begin{center} \textbf{\emph{{*}{*} You don't care about the exponent on x - just the factors with n inside {*}{*}}} \par\end{center}

What do I mean? Look at problem 2 again. Powers of $x$ don't matter, as we can write $x^{n+2}$ as $x^{2}\cdot x^{n}$ or $x^{3}\cdot x^{n-1},$ or in fact whatever we need. Problem 2 is tailor-made for using the third derivative, if we separate out enough powers of $x:$ \begin{eqnarray*} \sum_{n=0}^{\infty}n(n-1)(n-2)x^{n+2} & = & x^{5}\sum_{n=0}^{\infty}n(n-1)(n-2)x^{n-3}\\

& = & x^{5}\cdot\frac{6}{(1-x)^{4}}\\
& = & \frac{6x^{5}}{(1-x)^{4}.}

\end{eqnarray*} That rule becomes even more important for the ``difficult problem 3. We have exactly two factors with $n,$ so it should be related to the second derivative. With a little thought, you should realize we can reindex it: \begin{eqnarray*} \sum_{n=0}^{\infty}(n+2)(n+1)x^{n-2} & = & \sum_{n=2}^{\infty}(n)(n-1)x^{n-4}\\

& = & x^{-2}\sum_{n=2}^{\infty}n(n-1)x^{n-2}\\
& = & x^{-2}\cdot\frac{2}{(1-x)^{3}}\\
& = & \frac{2}{x^{2}(1-x)^{3}}.

\end{eqnarray*}

The key is that simple rule: we have two factors with $n,$ each

differing by one. This means we should look at using the second derivative. \end{document}

</source>